Diary of a wimpy kid : dog days - Kinney, Jeff (London, Puffin, 2011)
Split your sides laughing as Greg Heffley struggles with all the trials and tribulations of school, family and friends that come with being everyone's favourite wimpy kid!
Keywords: English Fiction